Probiotic Lactobacillus acidophilus FNCC 0051 Improves Pancreatic Histopathology in Streptozotocin-induced Type-1 Diabetes Mellitus Rats - Mardhatillah Sariyanti; Tiara Ayoe Andita; Noor Diah Erlinawati; Elvira Yunita; Ahmad Azmi Nasution; Kartika Sari; Nikki Aldi Massardi; Sylvia Rianissa Putri (The Indonesian Biomedical Journal, 2022)
BACKGROUND: Intestinal microbial dysbiosis and its metabolites can affect the immune activity of intestinal mucosal cells, causing insulitis and pancreatic β-cell death. Probiotic Lactobacillus acidophilus plays an important role in reducing inflammatory cytokines, hence improves oxidative stress that affects pancreatic β-cell apoptosis. Current study examined the feature of pancreatic histopathology affected by the administration of probiotic L. acidophilus in rats with type-1 diabetes mellitus (DM) induced by streptozotocin (STZ).METHODS: Twelve rats were induced by STZ at double dose of 50 mg/kgBB before administered with probiotic L. acidophilus at a dose of 1.5x10 8 or 1.5x10 9 CFU/mL/day, while other 4 rats were used as control. After 21 days of the L. acidophilus treatment, the average of fasting blood glucose (FBG) levels of rats were measured, then the pancreatic histopathology was assessed to evaluate the degree of insulitis in islet of Langerhans.RESULTS: The induction of STZ had been succeeded to increase blood glucose levels, which indicate DM condition. The highest FBG level after 21 days of treatment was found in DM group with glucose level of 512±81.51 mg/dL. The administration of probiotic L. acidophilus during 21 days treatment at both dose 1.5x10 8 and 1.5x10 9 CFU/mL/day significantly improved pancreatic histopathology (p=0.04 and p=0.034, respectively), with significant decrease on insulitis scores compared to DM group.CONCLUSION: The administration of L. acidophilus at both dose of 1.5x10 8 and 1.5x10 9 CFU/mL/day for 21 days can improve pancreatic histopathology of type-1 DM rats induced by STZ, therefore probiotic L. acidophilus may be potential as supplementation treatment for type-1 DM.KEYWORDS: Lactobacillus acidophilus, pancreatic histopathology, streptozotocin, type-1 diabetes mellitus